A Practical Guide for Researchers to Conduct Online Focus Group Discussions - Sattar, Kamran; Siddiqui, Durdana; Jokhio, Muhammad Faraz; Yusoff, Muhamad Saiful Bahri (Education in Medicine Journal, 2026)
This practical guide’s main goals are to assist researchers in understanding online focus group discussions (e-FGD), emphasise the need to obtain a range of viewpoints, and provide novices with a step-by-step approach to ensure successful preparation, execution, and analysis. e-FGD provides a convenient, accessible platform for gathering diverse opinions and experiences from participants across multiple sites, overcoming geographical barriers. In the current digital era, they accommodate participants’ schedules and increase flexibility while delivering fast, cost-effective insights. This guide provides easy-to-follow instructions supported by evidence from recent research. e-FGDs are particularly valuable in fields like medical education, revealing insights often missed in quantitative studies. Although there are obstacles such as limited resources, digital literacy, and connectivity issues, these challenges promote open, spontaneous conversations and more comprehensive data. Future research could explore artificial intelligence (AI)-based moderation, multilingual adaptation, and cross-cultural comparisons. By following this guide, researchers will be equipped to conduct e-FGDs effectively and foster inclusive, meaningful dialogue.